Adsorption mechanisms of self-organization of inorganic carrier – preparation of heterostructures of native enzymes - Kazdobin, Konstantin; Pershina, Katerina; Khodykina, Мariya; Trunova, Olena (My University, 2018)
The influence of heterostructures (core-shell) formed by the native enzyme preparation extracted from black radish and white cabbage, immobilized on inorganic carriers with different surface nature on electrochemical properties of obtained materials is shown. Depending on the nature of support the mechanism for the binding of enzymes and their activity vary by the rate of activation. Based on the voltammetry of immobilized enzyme drugs on inorganic supports, the possibility of using these heterostructures as a basis for the devices for energy storage is shown.
Keywords: native enzyme; immobilization; inorganic carrier; graphene; capacitor; нативний фермент; іммобілізація; неорганічний носій; графен; ємність